Fight club – whether to make architecture or blow it up! - Jarman, Dik (Intellect, 2015)
Dik Jarman has nearly thirty years of experience in the profession of architecture as well in stop motion animation winning multiple international awards in both endeavours. In this Chapter he describes the lessons that each profession had to offer its counterpart as well as their limitations. He discusses his own internal conflict that drove the separate pursuit of each profession and likens it to the narrator of 1999 film Fight Club where he is torn by his discontent of his white colour job and looked to “destroy something beautiful” ending up splitting himself into two. Dik uses examples of his work on productions with William S. Burroughs, Francis Ford Coppola, Oscar winner Adam Elliot and architectural practice Studio505.